Relationship Between Cadres Knowledge and Ability to Document Arumdalu Integrated Service Posts (Posyandu) Information System Reports - Devi Pramita Sari; Andi Zulkifli (Media Kesehatan Masyarakat Indonesia, 2025)
The high demands of administration and activities report at Integrated Service Posts (Posyandu) requiring cadres skills in documenting data accurately. In this field, the reality shows that many cadres lack adequate knowledge regarding. The Posyandu information system, especially the Arumdalu Posyandu. Therefore, this study aimed to determine the relationship between cadres' knowledge and ability to document reports on the Arumdalu Posyandu information system. The quantitative analytical research design used a cross-sectional, longitudinal (pre-post digital training), and mixed methods approach, complemented by Social Network Analysis (SNA). The research sample consisted of 60 Posyandu cadres at the Arumdalu Posyandu in the Sanggrahan Health Center working area, Sukoharjo Regency. Analysis was conducted univariately, bivariately using the Spearman Rank correlation test, multivariate with logistic regression, pre-post training test with Wilcoxon, qualitatively through FGDs, and SNA to map interactions between cadres. The results showed a significant relationship between cadres' knowledge and their ability to document reports (p = 0.003; r = 0.421). Multivariate analysis showed a significant effect of knowledge (OR = 3.42; 95% CI: 1.45–8.06), and education was also significant (OR = 2.87; 95% CI: 1.12–7.39). Longitudinal testing showed an average 22% increase in documentation skills after digital training (p < 0.001). Qualitative analysis identified motivation, workload, and institutional support as important factors, while SNA found the presence of key cadres as centers for information dissemination. In conclusion, increasing cadre capacity through digital training, supervision, institutional support, and utilizing cadres social networks is crucial for improving the quality of Posyandu cadres reporting.